ECONOMIC EFFECTS OF ECO-TOURISM - Štrbac, Maja; Hamović, Vladana (Economics of Agriculture, 2011)
Ecotourism involves travel to destinations with a recognizable preserved flora and fauna that are the primary attraction for tourists, with minimal environmental impact. There are two economic concepts in eco-tourism. These are the economic impact and economic value. The impacts of eco-tourism as an economic activity may be direct or indirect. Rural tourism is closely linked to ecotourism, which primarily reflected the favorable conditions of preserved nature, the environment, clean air, unpolluted rivers and lakes, rich flora and fauna, while spending time outdoors gives tourists the opportunity for walking, recreation, sports, organized tours to nearby caves, waterfalls, hunting and fishing, horseback riding, picking wild fruits and herbs, and other recreational and entertainment activities as well. The authors analyze the main economic activities in eco-tourism such as energy efficiency and creating conditions for community development, emphasizing the connection between eco and rural tourism.